Pour une éthique de l’environnement inspirée par le pragmatisme : l’exemple du développement durable - Alain Létourneau (VertigO)
We want to show here how pragmatism, understood in the light of three of its main thinkers and founders, Charles S. Peirce, William James and John Dewey, can totally renew our conception both of the theoretical and of the applied work in environmental ethics. But first we must explain what questions have structured the field of environmental ethics from its beginning, looking especially at the main discussions that have surfaced in the field since the 1970s. We also show what resources have been developed in the broader field of what we call here “society ethics”, a grouping into which we situate both biomedical ethics and applied ethics more generally. Here we place ourselves inside an applied ethics perspective, understood as differing from an applied principlism (cf Beauchamp and Childress, 2008). We also recall some of the main characteristics of pragmatism both generally and specifically on ethical questions, to show more clearly the main traits of a pragmatist outlook on those issues. To manifest more clearly what consequences this perspective gives on environmental issues, we treat briefly in conclusion the example of sustainable development.